PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING DIPADUKAN DENGAN MIND MAPPING TERHADAP PENINGKATAN MOTIVASI DAN HASIL BELAJAR BIOLOGI SISWA KELAS VII SMP 2 YPK MALANG - Lori, Astriani Rengu; Lestari, Purwaning Budi (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2017)
The purpose of this study is to improve the student’s motivation and learning outcomes through the application of guided inquiry learning models combined with mind mapping. This type of research is a Classroom Action Research that conducted in two cycles, each cycle consist of planning, action, observation and reflection. The subjects were firsth grade students of Junior High School YPK inJava. The data analysis in this studyusing descriptive statistical analysis. The results showed that the application of guided inquiry learning model combined with mind mapping can improve the student’s motivation and learning outcomes. That was showed by the increasing in the first cycle of classical learning completeness of 11.1% and an average value of 63.18 increase in cycle II 76.20% for mastery learning and average value of student learning at 80. In addition to improved learning outcomes as well increased motivation to learn as well as increased activity of the students. The conclusion is the application of guided inquirycombined with mind mapping can increase student’ motivation and learning outcomes.